Optimizing E-wom, Price Perception, and Content Marketing to Increase Purchasing Decisions on the Instagram Platform: Mengoptimalkan E-wom, Persepsi Harga, dan Pemasaran Konten untuk Meningkatkan Keputusan Pembelian di Platform Instagram - Adi Suparwo; Nabila Shafa Shalsabila (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2026)
This study aims to determine the description of e-WOM, price perception, and content marketing on purchasing decisions. Then, to test the partial influence of e-wom on purchasing decisions, price perception on purchasing decisions, and content marketing on purchasing decisions, and simultaneously regarding the influence of e-wom, price perception, and content marketing on purchasing decisions on the CV. Primar Lestari, Instagram platform. The data analysis used is a descriptive verification method with a purposive sampling method of 100 respondents. The results of the study showed that the description of el-wom, price perception, content marketing, and purchasing decisions were in the good category. Partially, el-wom and contelnt markelting did not have a significant effect on purchasing decisions, while pricel pelrcelption had a significant effect on purchasing decisions. Simultaneously, el-wom, pricel pelrcelption, and contelnt markelting significantly influelncel purchasing delcisions. The implications of this study emphasize that CV. Prima Lestari should focus on optimizing its pricing strategy to increase sales conversions. Theoretically, these results confirm that functional elements (price) still carry a higher weight in consumer decision-making on social media than communicative elements.